(untitled) (Quest Journal of Management and Social Sciences, 2022)
Background: Several developing nations that effectively moved from low to middle-income status are subsequently caught within the middle-income trap because of the recurring economic expansion. In this situation, what should policymakers do? Objective: The article attempted to examine the essential factors that can substantially influence Asian nations’ ability to avoid sinking into the middle-income trap. Finally, the research looked at factors that help Asia’s high-income countries stop getting into this trap as their economies develop. Method: The paper examines the elements that are crucial for Asian economies and should deter them from slipping towards the middle-income trap using qualitative as well as quantitative methods. The analysis section consists of two sections: a descriptive analysis of the time patterns of different variables based on nineteen Asian economies from 1990 to 2014, and empirical research using panel regression and a panel probit regression analysis using the countries’ income status as a binary variable to devise a possible policy recommendation. Result: According to studies, technological improvements, infrastructure development, and the demographic dividend are far more essential variables for overcoming the middle-income trap are technical improvements, infrastructure development, as well as the demographic dividend. Furthermore, governments in this area should implement optimal macroeconomic policies in order to promote growth without compromising economic stability. Conclusion: This study concludes that three main emphasis points should be examined when the middle-income trap needs to get addressed in the Asian region’s high-income nations’ growth path. They are appropriate R&D investments indicating technical advancement in research and innovation, development and realization of "soft" and "hard" infrastructure, and optimal use of the demographic dividend.